2013
DOI: 10.1103/physrevlett.110.096405
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Time-Reversal Symmetry Breaking for Spinless Fermions on a Triangular Lattice

Abstract: As a minimal fermionic model with kinetic frustration, we study a system of spinless fermions in the lowest band of a triangular lattice with nearest-neighbor repulsion. We find that the combination of interactions and kinetic frustration leads to spontaneous symmetry breaking in various ways. Time-reversal symmetry can be broken by two types of loop current patterns, a chiral one and one that breaks the translational lattice symmetry. Moreover, the translational symmetry can also be broken by a density wave f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Recently, the GL method was re-derived in the context of superfluid ultracold Fermi gases [2,3,4,5]. The GL approach was also applied to explain the phenomenon of the "1.5-type" superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the GL method was re-derived in the context of superfluid ultracold Fermi gases [2,3,4,5]. The GL approach was also applied to explain the phenomenon of the "1.5-type" superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the M-point charge density waves (i.e., s waves) have been found as ground states or leading instabilities of interacting electron models, in the context of triangular lattice [53], honeycomb lattice [54], and kagome lattice [55] models with extended Hubbard interactions, using Hartree-Fock and renormalization group methods. Similarly, a mean-field study of spinless electrons on the triangular lattice has reported spontaneous time-reversal symmetry breaking with M-point modulations [56]. Clearly, a full study of leading instabilities requires including the spin channel [53,55,[57][58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Metallic systems with non-trivial topological properties, generically referred to as topological Fermi liquids (TFLs) [6], have come to play an important role in the study of marginal and other non-Fermi liquid phenomena [7]. Various instances [8][9][10][11][12][13][14][15][16] of TFLs and topological Mott insulators (TMIs) at commensurate fillings have been realized on the honeycomb lattice using a combination of mean-field theory and numerics.…”
mentioning
confidence: 99%